Design Of a Public Reporting Application For Traffic Violations: A Case Study Of The Samarinda City Transportation Department - Yusva Awabil Chair; Muhammad Fahmi; Azahari Azahari (STMIK Widya Cipta Dharma, 2026)
This study aims to design a public reporting application for Traffic violations to assist the Samarinda City Transportation Department in improving the effectiveness of Traffic monitoring and law enforcement. The current problem lies in the reporting process, which is still conducted manually, resulting in delays in handling reports and limiting public participation in reporting Traffic violations. This study employed the Waterfall system development method, consisting of Requirement analysis, system design, implementation, testing, and maintenance stages. Research data were collected through observation, literature review, and field studies at the Samarinda City Transportation Department to comprehensively identify system Requirements. The results indicate that the implementation of the public reporting application for Traffic violations significantly increases the number of public reports, accelerates the response time for handling violations, and improves transparency and accountability in report management. The designed application also facilitates the public in submitting reports in real time through location data and violation documentation uploads. Furthermore, the application is expected to become an innovative solution in supporting Traffic law enforcement and improving the quality of public services in the transportation sector in Samarinda City. The system was developed using PHP (Hypertext Preprocessor) as the programming language and MySQL (My Structured Query Language) as the database management system managed through PhpMyAdmin. The system is also designed to provide easier access, improve report management efficiency, and support more responsive and sustainable Traffic monitoring.